“UNDUE PROCESS OF LAW” DALAM PERKARA PIDANA PERJUDIAN DENGAN TERDAKWA ANAK - Melani Melani (Jurnal Yudisial, 2011)
ABSTRACTThis article analyzes a decision of Bandung District Court. In this case, the Defendant (IR) was convicted of gambling with his friends (adults) in a public transportation with bets ranging from one to two thousand rupiahs. In examining the case, judges did not perform the procedure set out in the Juvenile Court Act (JCA), especially Articles 55, 57, and 58 Paragraph (2). From the beginning of the trial and during trial, IR was not accompanied by his parents, Legal Counsel, and Supervising Community. Prior to pronounce the verdict, the judge did not provide the opportunity for parents to express all the things that are beneficial to IR. This also disregards JCA, Article 59 Paragraph (1). All of these showed the undue process of law. Judge's decision was on the contrary to the JCA Article 59 Paragraph (2), because the judge did not consider the social study report. The judges punished IR imprisonment for 2 months 15 days based on the retributive (revenge) philosophy of punishment, which should be the restorative (recovery). It also suggested that IR should be returned to his parents. Keywords: undue process of law, juvenile delinguency, children rightsABSTRAKArtikel ini menganalisan putusan Pengadilan Negeri Bandung. Pada kasus ini, terdakwa (IR) telah didakwa bersama teman-temannya yang sudah dewasa yang bekerja di bidang transportasi umum dalam permainan taruhan yang bernilai ribuan. Dalam kajian terhadap kasus ini, hakim seharunya mengetahui lebih mendalam terkait undang-undang Peradilan Anak pasal 55, 57, dan 58. Dari awal persidangan, IR tidak didampingi oleh orang tuanya, pendamping hukum, dan atau supervsi dari komunitas pemerhati masalah anak. Dalam putusan, hakim tidak memberikan peluang bagi orang tuanya untuk mengungkapkan hal-hal yang menguntungkan IR. Pasal 59 UU Pengadilan anak mensyaratkan adanya hukum acara anak, sementara putusan hakim justru kebalikannya karena tidak mempertimbangkan hasil kajian sosial. Hakim memutuskan IR dihukum 2 bulan 15 hari berdasarkan filosofi hukuman, padahal seharusnya berdasarkan filosofi restoratif dan juga mengembalikan IR kepada orang tuanya. Kata kunci: hukum acara pengadilan anak, peradilan anak, hak anak